CGIAR’s Flagship Report: Rooted Apical Cuttings -Q & A. - International Potato Center (2025)
CGIAR’s first Flagship Report will be launched in April 2025. The report is being driven by decision-makers especially at the national level who have requested we present a portfolio of options where science has been shown to help them make informed decisions and navigate trade-offs – and have particularly requested examples that have decision-making tools that translate the science – in other words, not the science papers or technical reports.